2012
DOI: 10.2105/ajph.2012.300751
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Indoor Air Quality of Hookah Lounges

Abstract: Many states have implemented smoke-free workplace laws to protect employees and customers from exposure to secondhand smoke. However, exemptions in these laws have allowed indoor tobacco smoking in hookah lounges to proliferate in recent years. To describe the amount of secondhand smoke in hookah lounges, we measured the indoor air quality of 10 hookah lounges in Oregon. Air quality measurements ranged from "unhealthy" to "hazardous" according to Environmental Protection Agency standards, indicating a potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 7 publications
3
20
4
Order By: Relevance
“…Similar increases in levels of pollutants, such as PM2.5, BC, CO, and nicotine, have now been reported in several studies 25 26 33. This documented poor indoor air quality suggests that hookah bar workers, as well as patrons of hookah bars, inhale airborne particles and gases that can potentially cause adverse health effects 28–30.…”
Section: Discussionsupporting
confidence: 73%
“…Similar increases in levels of pollutants, such as PM2.5, BC, CO, and nicotine, have now been reported in several studies 25 26 33. This documented poor indoor air quality suggests that hookah bar workers, as well as patrons of hookah bars, inhale airborne particles and gases that can potentially cause adverse health effects 28–30.…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, air quality levels in the smoking rooms and adjacent rooms in hookah-smoking homes were found to be similar with those of hookah bars with multiple smokers and little to no ventilation 25 30…”
Section: Discussionmentioning
confidence: 84%
“…It is a global problem, primarily emanating from the Middle East,4 and as a result, countries like the UAE have enacted a number of laws concerning tobacco use and hookah use in the past decade 32. Virtually all that we know to date about air quality and health effects of hookah use and exposure to hookah-related SHS, however, comes from studies conducted in settings other than homes where hookah is smoked 20 25 29 30. This is the first study that we are aware of that investigates multiple air pollutants in homes where hookahs are smoked, demonstrating potentially hazardously high levels of all pollutants assessed in rooms where hookah was smoked and in the adjacent rooms.…”
Section: Discussionmentioning
confidence: 99%
“…The first published study on indoor air quality of hookah bars measured PM 2.5 in 10 hookah lounges in Oregon, USA 28. Those authors suggested that by comparison of the hookah smoke PM 2.5 to the USA.…”
Section: Discussionmentioning
confidence: 99%